TikTok's Impact on Senior High Students' English Speaking Engagement - Adrin Kristian Putra; Yuliati (Universitas Islam Negeri Raden Intan Lampung, 2025)
The study explores the impact of TikTok content on English speaking engagement among 11th grade students. Fear of making mistakes and a lack of real-world practice opportunities are significant psychological barriers that make speaking a challenge for English as a Foreign Language (EFL) students. They often struggle with limited vocabulary, pronunciation issues, and grammatical errors, which further hinder their spoken fluency. The problems, however, can be addressed by using engaging and relatable content from platforms like TikTok to increase motivation and confidence. With the rise of social media as a learning tool, TikTok has emerged as a platform for informal language acquisition and learning. The research employs a thematic analysis methodology, investigating individual students’ learning experience, teachers' perception within the learning process, and TikTok audience when given certain English speaking TikTok content. The primary research questions investigate how TikTok’s English-speaking content can contribute to the engagement of students. The findings provide practical insights for educators on integrating modern technology into language instruction. Ultimately, this investigation seeks to fill a gap in existing research on TikTok's influence on EFL speaking comprehension, offering valuable implications for both theoretical understanding and practical application in language education.